Planar‐Chiral Ferrocene‐Based N‐Heterocyclic Carbene Ligands. Issue 70 (28th November 2018) - Yoshida, Kazuhiro; Yasue, Risa
Abstract: In the last few decades, N‐heterocyclic carbene (NHC) ligands, characterized by attractive features, have increased their presence in transition‐metal catalysis. However, chiral NHC ligands still require further design enhancement to realize far more exciting synthetic applications. This review documents advances in chiral NHC ligands, focusing on planar‐chiral ferrocene‐based NHCs. As the basic shape of most classes of NHC rings is planar, it seems rational to employ a planar‐chiral element in the design of chiral NHC ligands. Abstract : Planar‐chiral ferrocene ligands : Chiral N‐heterocyclic carbene (NHCs) ligands offer the possibility for use in a wide range of transition‐metal catalyzes. In this review, an overview is presented of the developing field, focusing on planar‐chiral ferrocene‐based NHC ligands.